MEDICAL-PSYCHOLOGICAL ASPECTS OF EXPRESSION OF FEAR IN ADOLESCENT PERIOD AND WAYS OF ITS ELIMINATION - Tursunbayeva Zarnigor Azamat Qizi; Tursunbaeva Zarnigor Azamata Qizi; Tursunbayeva Zarnigor Azamat Qizi (Scholar Express Journals, 2023)
The article analyzes the specific characteristics of emotional states that appear in adolescence.
Keywords: Adolescence; emotion